2017
DOI: 10.1002/lary.26606
|View full text |Cite
|
Sign up to set email alerts
|

Postinfectious olfactory loss: A retrospective study on 791 patients

Abstract: Objectives/Hypothesis: Postinfectious olfactory loss is among the most common causes of olfactory impairment and has substantial negative impact on patients' quality of life. Recovery rates have been shown to spontaneously improve in most of patients, usually within 2 to 3 years. However, existing studies are limited by small sample sizes and short follow-up. We aimed to assess the prognostic factors for recovery in a large sample of 791 patients with postinfectious olfactory disorders.Study Design: Retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 29 publications
6
99
1
1
Order By: Relevance
“…However, all patients subjectively continued to report smell loss. In light of recent findings suggesting spontaneous recovery is possible even after a year, we should consider our results in that context. However, the direct temporal relationship of the improvement in our patients after injection causes us to consider this a finding worth investigating further.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, all patients subjectively continued to report smell loss. In light of recent findings suggesting spontaneous recovery is possible even after a year, we should consider our results in that context. However, the direct temporal relationship of the improvement in our patients after injection causes us to consider this a finding worth investigating further.…”
Section: Discussionmentioning
confidence: 76%
“…The etiology of olfactory dysfunction is quite varied, including postviral, post‐traumatic, and idiopathic loss of smell. Unfortunately, with these etiologies, the likelihood of spontaneous recovery is generally poor, with only approximately one‐third of people regaining function and the duration of loss negatively correlating with recovery rate . Treatment for olfactory dysfunction is also limited.…”
Section: Introductionmentioning
confidence: 99%
“…Former studies suggest that spontaneous recovery can be observed in approximately one-third of postinfectious patients. [24][25][26] Although we are unable to exclude the possible effects of spontaneous recovery, the improvement in our training cohort occurred approximately within 6 months, as opposed to at least the 12-month period typical of untreated patients. 24,26 Further studies with placebo control should be performed.…”
Section: Discussionmentioning
confidence: 97%
“…Respiratory tract infections can cause direct damage to neurons in the olfactory epithelium. Postinfectious olfactory dysfunction is seen frequently after a respiratory tract infection and accounts for 18% to 45% of all cases of anosmia 8 . Recent reports have suggested that anosmia and ageusia could be potential symptoms of COVID‐19 5,9,10 .…”
Section: Discussionmentioning
confidence: 99%